Liberdade e diversidade religiosa em Anápolis: construção da harmonia na pluralidade - Souza Filho, Oscar Vasconcelos de (2006)
This dissertation is the result of a study, in the municipality of Anápolis, in the current context of Religious Education in a pluralistic world. Proposes an alternative process in leading people to maturity in open criticism, in a process which leads to learning more pleasurable. The starting point is the ecumenical attitude with the corner stone of the constitutional construction of religious freedom and Religious Education, which is a mere consequence of religious freedom. The work concludes that the nonproselytism promotes a civilization through social harmony.